APAKAH BESARAN INSENTIF, KOMPLEKSITAS TUGAS, DAN PENGETAHUAN BERPENGARUH TERHADAP PERTIMBANGAN AUDIT? - Mega Ayu Lestari; Hasnawati Zainal (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2019)
This research aims to examine and analyze the influence of work incentives, task complexity, and knowledge of auditors to audit judgment. This research is a qualitative research using primary data from the questionnaire. The sampling method used is convenience sampling, obtained with a sample of 144 auditor respondents from 21 Public Accountants Firm in DKI Jakarta Region registered in Directorate of Indonesian Institute of Certified Public Accountants. The data analysis technique is Structural Equation Model (SEM) based on Analysis Of Moment Structure (AMOS) with AMOS analysis tool 24. This research shows that work incentive and auditor's knowledge have positive and significant influence to audit judgment, while for task complexity has a negative and significant effect on audit judgment.